Anticoagulant Therapy in Pregnant Women with Mechanical Heart Valves: Italian Federation of Centers for Diagnosis and Surveillance of the Antithrombotic Therapies (FCSA) Position Paper - Campello, Elena; Bucciarelli, Paolo; Catalani, Filippo; Erba, Nicoletta; Squizzato, Alessandro; Poli, Daniela; Scientific Reviewer Committee; Lip, Gregory Y. H.; Roldan, Vanessa; Basili, Stefania; Langer, Florian; Lewey, Jennifer (Thrombosis and Haemostasis, 2024)
The management of anticoagulant therapy in pregnant women with mechanical heart valves (MHVs) is difficult and often challenging even for clinicians experienced in the field. These pregnancies, indeed, are burdened with higher rates of complications for both the mother and the fetus, compared to those in women without MHVs. The maternal need for an optimal anticoagulation as provided by vitamin K antagonists is counterbalanced by their teratogen effect on the embryo and fetus. On the other hand, several concerns have been raised about the efficacy of heparins in pregnant women with MHVs, considering the high risk of thrombotic complications in these patients. Therefore, numerous clinical issues about the management of pregnant women with MHVs remain unanswered, such as the selection of the best anticoagulant agent, the optimal anticoagulation levels to be achieved and maintained, and the evaluation of long-term effects for both the mother and the fetus. Based on a comprehensive review of the current literature, the Italian Federation of the Centers for the Diagnosis and the Surveillance of the Antithrombotic Therapies (FCSA) proposes experience-based suggestions and expert opinions. Particularly, this consensus document aims at providing practical guidance for clinicians dealing with pregnant women with MHVs, to optimize maternal and fetal outcomes while guaranteeing adequate anticoagulation. Finally, FCSA highlights the need for the creation of multidisciplinary teams experienced in the management of pregnant women with MHVs during pregnancy, delivery, and postpartum, in order to better deal with such complex clinical issues and provide a comprehensive counseling to these patients.
Keywords: pregnancy; prosthetic heart valves; thromboembolism; heparin; vitamin K antagonists